2022
DOI: 10.1186/s13071-022-05199-6
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus spp. and genotypes infecting humans in Tibet Autonomous Region of China: a molecular investigation with near-complete/complete mitochondrial sequences

Abstract: Background Molecular markers are essential to identify Echinococcus species and genotypes in areas with multiple Echinococcus species to understand their epidemiology and pathology. Tibet Autonomous Region (TAR) is one of the areas worst hit by echinococcosis. However, molecular epidemiology is still missing among echinococcosis patients in TAR. This research explored the Echinococcus species and genotypes infecting humans in TAR and the population diversity and the possible origin of G1 in TAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…A previous attempt using this approach succeeded in identifying the global diffusion routes and origin of the closely related parasite E chinococcus granulosus . 19 , 54 The present study supported 19 diffusion routes of E. multilocularis , including those into Hokkaido, some of which align with previous findings, such as invasions of European strains into North America. 55 , 56 However, the results should be interpreted cautiously because there is a lack or shortage of datasets from regions where E. multilocularis is prevalent, such as Russia and several European countries, including Germany and Switzerland.…”
Section: Discussionsupporting
confidence: 91%
“…A previous attempt using this approach succeeded in identifying the global diffusion routes and origin of the closely related parasite E chinococcus granulosus . 19 , 54 The present study supported 19 diffusion routes of E. multilocularis , including those into Hokkaido, some of which align with previous findings, such as invasions of European strains into North America. 55 , 56 However, the results should be interpreted cautiously because there is a lack or shortage of datasets from regions where E. multilocularis is prevalent, such as Russia and several European countries, including Germany and Switzerland.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, AE is more restricted in certain geographical regions, especially in the Northern Hemisphere [ 2 ]. A molecular investigation of near-complete/complete mitochondrial sequences of 92 patients’ samples from Tibet Autonomous Region (TAR) identified that the main Echinococcus species and genotypes infecting humans in TAR were Echinococcus granulosus sensu stricto G1 followed by G6 of Echinococcus canadensis (6.52%), and Echinococcus multilocularis (2.17%) [ 30 ]. However, in Shiqu County on the Tibetan Plateau of Sichuan Province, AE is more prevalent with a prevalence of 3.58%, which is significantly higher than the prevalence of CE at 2.31%, as reported in an ultrasound-based prevalence study screening on 84,742 residents [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parasitology and epidemiology require mitochondrial gene genotyping of E. granulosus s.l. [ 72 ]. Studies of parasite diversity and population structure using mitochondrial genes are ideal.…”
Section: Methods For Diagnosis Of Cystic Echinococcosis In Intermedia...mentioning
confidence: 99%
“…Due to their diversity, specific mitochondrial genes, including COX1 and ND1 , are targeted for genetic studies [ 74 ]. PCR is used to amplify mitochondrial genes and increase the quantity of genetic material in mitochondria [ 72 ]. Genetic sequences of mitochondria are determined using DNA sequencing technologies like Sanger and Next-Generation Sequencing (NGS) [ 75 ].…”
Section: Methods For Diagnosis Of Cystic Echinococcosis In Intermedia...mentioning
confidence: 99%